A Prototype Biomarker Detector Combining Biomarker Extraction and Fixed Temperature PCR. (August 2016) - Russ, Patricia K.; Karhade, Aditya V.; Bitting, Anna L.; Doyle, Andrew; Solinas, Francesca; Wright, David W.; Haselton, Frederick R.
PCR is the most sensitive molecular diagnostic available for infectious diseases. The goal for low-resource settings is a simple, inexpensive instrument. Toward this goal, we previously published a self-contained sample preparation instrument that uses magnetics and prearrayed reagents in thin tubing to extract nucleic acids and perform isothermal amplification and detection of extracted biomarkers. To incorporate PCR thermal cycling, after biomarker is magnetically extracted from a patient sample, the section of tubing containing the extracted biomarker and PCR reagents is alternately positioned within two constant temperature blocks. This instrument was evaluated initially by extracting and amplifying a 140 bp fragment of the IS6110 sequence of tuberculosis from TE buffer. The mean cycle threshold for 5 × 10 6 copies of IS6110 was 25.5 ± 1.5 cycles ( n = 4), which was significantly different from negative control samples (34.0 ± 2.6 cycles; n = 3). Using a more clinically relevant sample, we extracted and amplified Plasmodium falciparum DNA from malaria-infected human blood cultures. The average cycle threshold for 1% parasitemia samples was 24.7 ± 1.5 cycles ( n = 3) and significantly different from negatives (31.5 ± 2.1 cycles; n = 3). This approach integrates biomarker extraction, PCR amplification, and detection in a simple, linear tubing design with potential for use as a low-resource instrument.